Update on the distribution of Aedes albopictus (Diptera: Culicidae) in Misiones, Argentina - Arturo A. Lizuain; Marina Leporace; María Soledad Santini; María Eugenia Utgés; Nicolás Schweigmann (Revista do Instituto de Medicina Tropical de São Paulo)
ABSTRACT The Asian tiger mosquito ( Aedes albopictus, Diptera: Culicidae) has spread rapidly in the last 30 years from its native region in Southeast Asia. In Argentina, studies on its potential distribution suggest that this species could be found in temperate zones of the province of Buenos Aires. However, since its initial detection in 1998 Ae. albopictus is bounded to the subtropical province of Misiones. To evaluate the presence and abundance of Ae. albopictus in the Northeast of Argentina, we preliminarily evaluated the presence of this vector by analyzing its presence in tires of 20 cities belonging to the province of Misiones and four cities in Northern Corrientes, and then performed an evaluation of the vector in the towns where the vector was detected. Aedes albopictus was present only in two cities of Misiones: Eldorado and Colonia Aurora. Aedes aegypti and Ae . albopictus accounted for 86% of the individuals collected in the domiciles of both towns. In Colonia Aurora both species were in similar abundances suggesting a co-dominance. The present study extends the austral distribution of Ae. albopictus in Argentina to the city of Colonia Aurora where the highest abundance recorded in Argentina was detected. Nevertheless, the reasons of its bounded distribution in the region are not known.